Relationship between volume and outcome for surgery on congenital diaphragmatic hernia: a systematic review - Morche, Johannes; Mathes, Tim; Jacobs, Anja; Pietsch, Barbara; Wessel, Lucas; Gruber, Sabine; Neugebauer, Edmund A. M.; Pieper, Dawid (Journal of pediatric surgery, 2020)
Background - Congenital diaphragmatic hernia (CDH) is a rare and life-threatening anomaly that needs surgical therapy after clinical stabilization of the neonate. Given an existing volume-outcome relationship for other high-risk, low volume procedures, we aimed at examining the relationship between hospital or surgeon volume and outcomes for surgery on CDH. - Methods - We conducted a systematic search in multiple databases in September 2019 and searched for additional literature. We assessed risk of bias of included studies using ROBINS-I and synthesized results in a structured narrative way using GRADE. - Results - We included 5 cohort studies on hospital volume. Results for in-hospital mortality, one-year mortality and length of stay are inconclusive. The certainty of the evidence was very low for all outcomes, due to risk of bias, inconsistency and imprecision. We did not identify any study on surgeon volume. - Conclusion - Due to the very low certainty of the evidence it is uncertain whether higher hospital volume is associated with favorable outcomes for neonates undergoing surgery for CDH. There is no evidence on the relationship between surgeon volume and outcomes. Future studies should use more rigorous methodology and analyze additional outcomes to allow for more meaningful inferences. - Level of Evidence - III - Systematic review registration - PROSPERO (CRD42018090231).